2-[(4-Benzhydrylpipérazin-1-yl)méthyl]acrylonitrile - Mohamed Lotfi Efrit (Acta Crystallographica Section E, 2008)
In the title compound, 2-[(4-benzhydrylpiperazin-1-yl)methyl]acrylonitrile, C21H23N3, the substituted piperazine ring adopts a chair conformation and the dihedral angle between the mean planes of the aromatic rings is 71.61 (8)°.